Theoretical study on volcanic plume SO 2 and ash retrievals using ground TIR camera: Sensitivity analysis and retrieval procedure developments - Corradini, S; Tirelli, C; Gangale, G; Pugnaghi, S; Carboni, E (2010)
In this paper, a sensitivity analysis and procedure development for volcanic-plume sulfur dioxide and ash retrievals using ground thermal infrared camera have been carried out. The semiconductor device camera, considered as a reference, has a spectral range of 8-14 ìm with noise equivalent temperature difference that is better than 100 mK at 300 K. The camera will be used to monitor and assess the hazards of Mt. Etna volcano to mitigate the risk and impact of volcanic eruptions on the civil society and transports. A minimum number of filters have been selected for sulfur dioxide (SO 2) and volcanic ash retrievals. The sensitivity study has been carried out to determine the SO 2 and volcanic ash minimum concentration detectable by the system varying the camera geometry and the atmospheric profiles. Results show a meaningful sensitivity increase considering high instrument altitudes and low camera-elevation angles. For all geometry configurations and monthly profiles, the sensitivity limit varies between 0.5 and 2 g.m -2 for SO 2 columnar abundance and between 0.02 and 1 for ash optical depth. Two procedures to detect SO 2 and ash, based on the least square fit method and on the brightness temperature difference (BTD) algorithm, respectively, have also been proposed. Results show that high concentration of atmospheric water vapor columnar content significantly reduces the ash-plume effect on the BTD. A water vapor-correction procedure introduced improves the ash retrievals and the cloud discrimination in every season, considering all the camera geometries. © 2009 IEEE.